2018
DOI: 10.1186/s13014-018-1149-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary function and quality of life after radiotherapy for prostate cancer in patients with prior history of surgical treatment for benign prostatic hyperplasia

Abstract: BackgroundTo evaluate long-term IPSS score and urinary quality of life after radiotherapy for prostate cancer, in patients with prior history of surgical treatment for benign prostatic hyperplasia (BPH).MethodsIn this retrospective study, we reviewed medical records of patients treated in our department, between 2007 and 2013 with surgery for BPH followed by radiotherapy for localized prostate cancer. Patients were contacted to fill in IPSS questionnaire and they were also asked for urinary quality of life. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In our study we observed that the volume of the intraprostatic postsurgical cavity was correlated with an increased risk of developing genitourinary toxicities. This association was not observed in a series of 59 patients treated with normofractionated EBRT and a prior medical history of surgical treatment of BPH (including eight cases treated with adenomectomy) [21]. Nevertheless, direct comparison between the two studies cannot be carried out, as to the best of our knowledge our study was the only one to estimate the resection cavity volume on the planning MRI, in contrast to the other study that was based on the pathology weight of resected prostate.…”
Section: Discussionmentioning
confidence: 66%
“…In our study we observed that the volume of the intraprostatic postsurgical cavity was correlated with an increased risk of developing genitourinary toxicities. This association was not observed in a series of 59 patients treated with normofractionated EBRT and a prior medical history of surgical treatment of BPH (including eight cases treated with adenomectomy) [21]. Nevertheless, direct comparison between the two studies cannot be carried out, as to the best of our knowledge our study was the only one to estimate the resection cavity volume on the planning MRI, in contrast to the other study that was based on the pathology weight of resected prostate.…”
Section: Discussionmentioning
confidence: 66%
“…Also, there is a concern that radical prostatectomy can be overtreatment as some patients will be reported as pT0. Radiotherapy is an effective treatment method with acceptable toxicity in patients who underwent TURP, incontinence rates are slightly higher compared to the patients without TURP (24,25). In this study, data on the continence status of patients who underwent radical prostatectomy and radiotherapy are lacking.…”
Section: Discussionmentioning
confidence: 97%
“…53 Late urinary toxicity rate was diminished in patients treated by modern irradiation techniques such as IMRT. 47 Zapatero et al 54 demonstrated that late urinary complications with high-dose IMRT compared with 3DCRT were lower despite higher radiation dose (80.7 Gy vs 78.7 Gy, p<0.001).…”
Section: Treatmentsmentioning
confidence: 99%
“…The incidence of severe long-term urinary toxicities is similar to those without a history of TURP. 47 Devisetty et al reported severe GU toxicity in patients who underwent external beam radiotherapy (EBRT) after TURP, but toxicity tends not to persist. 48 Mélanie Guilhen et al 47 reported External RT is a good option without a major hazard for urinary toxicity in a patient with a history of previous TURP.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation